Autophagy Constitutes a Protective Mechanism against Ethanol Toxicity in Mouse Astrocytes and Neurons - Pla, Antoni (PLoS One, 2016)
Ethanol induces brain damage and neurodegeneration by triggering inflammatory processes in glial cells through activation of Toll-like receptor 4 (TLR4) signaling. Recent evidence indicates the role of protein degradation pathways in neurodegeneration and alcoholic liver disease, but how these processes affect the brain remains elusive. We have demonstrated that chronic ethanol consumption impairs proteolytic pathways in mouse brain, and the immune response mediated by TLR4 receptors participates in these dysfunctions. We evaluate the in vitro effects of an acute ethanol dose on the autophagy-lysosome pathway (ALP) on WT and TLR4(-/-) mouse astrocytes and neurons in primary culture, and how these changes affect cell survival. Our results show that ethanol induces overexpression of several autophagy markers (ATG12, LC3-II, CTSB), and increases the number of lysosomes in WT astrocytes, effects accompanied by a basification of lysosomal pH and by lowered phosphorylation levels of autophagy inhibitor mTOR, along with activation of complexes beclin-1 and ULK1. Notably, we found only minor changes between control and ethanol-treated TLR4(-/-) mouse astroglial cells. Ethanol also triggers the expression of the inflammatory mediators iNOS and COX-2, but induces astroglial death only slightly. Blocking autophagy by using specific inhibitors increases both inflammation and cell death. Conversely, in neurons, ethanol down-regulates the autophagy pathway and triggers cell death, which is partially recovered by using autophagy enhancers. These results support the protective role of the ALP against ethanol-induced astroglial cell damage in a TLR4-dependent manner, and provide new insight into the mechanisms that underlie ethanol-induced brain damage and are neuronal sensitive to the ethanol effects.